Evaluation-Value Added Intellectual Coefficient (Ev-VAIC) Model Expansion : The New Measurement Model for Intellectual Capital - Santy Mayda, Batubara; Salawati, Sahari; Mohammad, Jais (Human Resource Management Academic Research Society (HRMARS), 2021)
This conceptual paper provides a theoretical discussion to design a new measurement model of intellectual capital by using the organization's Input and Output, which have been categorized into the organization value-added element to produce a more stringent and comprehensive intellectual capital component. This paper proposes a model with each domain have been defined as a set of indicators used for the next quantitative evaluation. This expansion of intellectual capital model enables organizations to pay more attention to the organization assets, which being as value-added category (capital employed and intellectual capital), that have not been well-connected in the literature previously. In addition, this paper attempt to understand the intellectual capital components and evaluate its developing tendency periodically in the future (the finance management field) as the longterm and sustainable competitive advantages.